Kearifan Lokal Manortor : Sebagai Jembatan Budaya dan Spiritualitas Batak Tarian Untuk Tuhan - Winda Kurniati Situmorang (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
Manortor is a traditional Batak dance, which has long been an integral part of the culture and social life of the Batak people themselves. This dance, usually performed in traditional celebrations such as weddings, births, and other traditional ceremonies, functions as an expression of joy, prayer, and respect for ancestors. However, along with the entry of Christianity into the Batak community, Manortor underwent a significant transformation, shifting from a ritual of respect for ancestral spirits to a medium of worship and expression of faith in God. In the context of Christian theology, "Manortor" is now understood not only as a traditional dance, but also as a form of respect, welcoming, and praise to God, manortor is not just an ordinary dance but there is an offering (offering the body) to express gratitude through body movements accompanied by gondang, manortor as a bridge between culture and Theology itself by maintaining cultural traditions and remaining faithful to the teachings of Christianity